Zimbabwe : Rural Electrification Study - World Bank (Washington, DC, 2014)
This report aims to document the picture of rural electrification in Zimbabwe emerging from detailed information gathering surveys. In addition, elements are highlighted that could feed into the process of developing a coherent rural energy and electrification strategy. The report, based on surveys, interviews, and other data-gathering exercises, is divided into seven chapters as follows: Chapter 1 presents a general background of the Zimbabwean energy sector, along with the methodologies that were used to collect data. Chapter 2 considers rural energy demand, presenting information on energy end-use, the energy services delivered, and their costs. Also, it outlines the seasonal activities giving rise to energy demand. Chapter 3 describes the dynamics of energy supply and the trends and opportunities arising from the current situation. Chapter 4 discusses issues that any successful rural electrification policy will need to address, including affordability and geographic disparity. In order to identify the suggested policy elements within the current energy sector structure, Chapter 5 describes the prevailing institutional and regulatory situation in Zimbabwe. It also describes on-going and planned energy sector activities so that policy elements acknowledge and build on these. Chapter 6 recommends policy elements from which a viable strategy for rural energy and electrification might be formulated. Chapter 7 draws some brief conclusions.